The Atlantic forest of South America : (Island Press, 2003)
The Atlantic Forest of Brazil, Paraguay, and Argentina is one of the most devastated and most highly threatened ecosystem on the planet; less than eight percent of the original forest remains and is facing intense population pressures from all sides. The Atlantic Forest of South America presents a detailed assessment of the state of biodiversity in the Atlantic Forest. Separate sections examine each of the three countries that are home to the forest, beginning with a brief overview that explores the dynamics of biodiversity loss in that country and outlines the topics to be addressed. Following the overview are individual chapters that analyze